Water-Level Changes in the Wells of Kamchatka at the Time of the Mw 7.6, April 20, 2006 Olyutorskii Earthquake - Kopylova G.N.; Smolina N.N. (My University, 2010)
The seismic waves excited by the Mw 7.6 Olyutorskii earthquake that occurred on April 20, 2006 in the Koryak Upland gave rise to water-level changes in five wells situated in continental areas of Kamchatka at hypocentral distances of 750–1150 km. We describe the effects due to seismic waves, as well as the water-level anomalies for February–April 2006 before the earthquake. We used an original technique for the processing of water-level records based on the study of barometric and tidal water-level responses in order to estimate the volume strain in water-saturated rocks during synchronous level variations at two wells. We discuss possible mechanisms for producing anomalous water-level changes due to elastic deformation of monitored groundwater reservoirs and to crack dilatancy in the water-saturated rocks.
Keywords: 37.31.19 Сейсмология; 38.61.15 Динамика и режим подземных вод; Olyutorskii earthquake